Identification of Factors Affecting Employee Performance: Systematic Literature Review - Fitriatu Lam’ah; Rofi Rofaida (Budapest International Research and Critics University, 2022)
Human Resources or employees are strategic assets for the organization. High or low organizational productivity and whether or not the goals are achieved organization is influenced by employee performance. The purpose of this research is to know the factors that affect employee performance. Method used is a Systematic Literature Review, with the database source coming from Scopus. Data is limited by the year of publication, namely 2017 to 2021, journal published in English, and has citations above 33. A total of 25 journals selected for research. From the results of the review, identified factors that are often used in research and can improve performance including: leadership, engagement, motivation, organizational culture, commitment, human resource management practices, and the work environment. Leadership was found in 11 journals out of 25 journals. While the factor that reduce performance include: job insecurity, anxiety, emotional exhaustion, justice differentiation, and job disruption. Job insecurity found in 2 journals out of 25 journals.